Co-teaching in higher education: implications for teaching, learning, engagement, and satisfaction - Zach, Sima; Avugos, Simcha (Frontiers in Sports and Active Living, 2024)
This study examined the impact of co-teaching on students and lecturers, assessing its benefits and drawbacks, and suggesting ways to enhance collaborative learning. Fifty undergraduate student teachers participated in two sports sciences seminar courses jointly taught by two lecturers. Data was collected via student reflections; course evaluation feedback; word clouds; and teacher reflections. Thematic analysis was used for qualitative data. The findings indicate that the short intensive seminar course resulted in three parallel processes: emotional, students transitioning from negative feelings of chaos, frustration, and a sense of incompetence to positive feelings of satisfaction and sense of accomplishment; social, students learning to listen, request assistance, support, encourage, and collaborate; and cognitive, students learning to ask fruitful questions, plan experiments, summarize, and present. Nevertheless, the time and effort demands involved in the planning and management of such courses may constitute a significant barrier to the future implementation of this teaching method.In terms of course outcomes, no indications of higher quality were seen compared to traditional instruction. Drawing on the symbolic interactionism theory, the study advocates for preparing students for inclusive and collaborative learning environments to improve academic engagement and success.